MR‐proADM as a Prognostic Marker in Patients With ST‐Segment–Elevation Myocardial Infarction—DANAMI‐3 (a Danish Study of Optimal Acute Treatment of Patients With STEMI) Substudy. Issue 11 (18th May 2018) - Falkentoft, Alexander C.; Rørth, Rasmus; Iversen, Kasper; Høfsten, Dan E.; Kelbæk, Henning; Holmvang, Lene; Frydland, Martin; Schoos, Mikkel M.; Helqvist, Steffen; Axelsson, Anna; Clemmensen, Peter; Jørgensen, Erik; et al.
Abstract : Background: Midregional proadrenomedullin (MR‐proADM) has demonstrated prognostic potential after myocardial infarction (MI). Yet, the prognostic value of MR‐proADM at admission has not been examined in patients with ST‐segment–elevation MI (STEMI). Methods and Results: The aim of this substudy, DANAMI‐3 (The Danish Study of Optimal Acute Treatment of Patients with ST‐segment–elevation myocardial infarction), was to examine the associations of admission concentrations of MR‐proADM with short‐ and long‐term mortality and hospital admission for heart failure in patients with ST‐segment–elevation myocardial infarction. Outcomes were assessed using Cox proportional hazard models and area under the curve using receiver operating characteristics. In total, 1122 patients were included. The median concentration of MR‐proADM was 0.64 nmol/L (25th–75th percentiles, 0.53–0.79). Within 30 days 23 patients (2.0%) died and during a 3‐year follow‐up 80 (7.1%) died and 38 (3.4%) were admitted for heart failure. A doubling of MR‐proADM was, in adjusted models, associated with an increased risk of 30‐day mortality (hazard ratio, 2.67; 95% confidence interval, 1.01–7.11; P =0.049), long‐term mortality (hazard ratio, 3.23; 95% confidence interval, 1.97–5.29; P <0.0001), and heart failure (hazard ratio, 2.71; 95% confidence interval, 1.32–5.58; P =0.007). For 30‐day and 3‐year mortality, the area under the curve for MR‐proADM was 0.77 and 0.78, respectively. For 3‐year mortality, area under the curve (0.84) of the adjusted model marginally changed (0.85; P =0.02) after addition of MR‐proADM. Conclusions: Elevation of admission MR‐proADM was associated with long‐term mortality and heart failure, whereas the association with short‐term mortality was borderline significant. MR‐proADM may be a marker of prognosis after ST‐segment–elevation myocardial infarction but does not seem to add substantial prognostic information to established clinical models. Clinical Trial Registration: URL: http:/www.ClinicalTrials.gov /. Unique identifiers: NCT01435408 and NCT01960933.